2009
DOI: 10.1177/152692480901900408
|View full text |Cite
|
Sign up to set email alerts
|

Induction Immunosuppression for Orthotopic Heart Transplantation: A Review

Abstract: At present, the unrestricted use of induction for all patients does not seem prudent. Induction should be individualized for each patient on the basis of a well-designed protocol, careful analysis of the transplant center's demographics, and the effectiveness and safety profiles of the regimens used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The anti-CD25 antibody, basiliximab, is a nondepleting agent that prevents the binding of interleukin 2 to its receptor, resulting in decreased T-cell proliferation. 10,11 Depleting agents target various antigens on the surface of T and B cells, resulting in cell lysis (cytolysis), which produces significant lymphocyte depletion. Depleting agents that target multiple antigens (CD2, CD3, CD4, CD8, CD11a, CD18, CD25, CD44, CD45, HLA) on the lymphocyte surface are considered polyclonal.…”
Section: Progress In Transplantation Vol 22 No 4 December 2012mentioning
confidence: 99%
“…The anti-CD25 antibody, basiliximab, is a nondepleting agent that prevents the binding of interleukin 2 to its receptor, resulting in decreased T-cell proliferation. 10,11 Depleting agents target various antigens on the surface of T and B cells, resulting in cell lysis (cytolysis), which produces significant lymphocyte depletion. Depleting agents that target multiple antigens (CD2, CD3, CD4, CD8, CD11a, CD18, CD25, CD44, CD45, HLA) on the lymphocyte surface are considered polyclonal.…”
Section: Progress In Transplantation Vol 22 No 4 December 2012mentioning
confidence: 99%
“…These agents act through a combination of direct ligand: receptor blockade, receptor down regulation (triggering removal of IL-2Ra from the cell surface without signaling), and antibodydependent cell-mediated cytotoxicity (ADCC) through activation and recognition by NK cells. First approved for kidney grafts in 1997, both antibodies continue to undergo clinical trials for various transplant indications (Poirier 2004;Delgado and Ross 2004;Van Gelder et al 2004;Ensor et al 2009). …”
Section: Allograft Transplantationmentioning
confidence: 99%
“…Although donor-related factors are not thought to increase risk of rejection or worsening renal dysfunction, these might be associated with insufficient cardiac performance in the early post-HTx period or high incidence of therapy is a strategy for improving clinical prognosis or making their managements easier in these high-risk HTx recipients, 1,2 and is administered to ~50% of all adult HTx recipients worldwide. 1, 3 Nevertheless, studies have shown no definitive evidence of its benefits. 1,4,5 Basiliximab selectively blocks interleukin-2 (IL-2), binding to its receptors (IL-2R) in activated T-lymphocytes, thereby inhibiting IL-2-mediated activated T-lymphocyte proliferation.…”
Section: Patient Selection and Study Protocolmentioning
confidence: 99%